Peningkatan Kapasitas Sumber Daya Manusia melalui Pelatihan Operator Wheel Excavator - Sadat NS Sidabutar; Impol Siboro; Marsius Ferdnian; Komeyni Rusba; Aminoto Kalter; Silvanus Parayu Prana Warman (Universitas Pahlawan Tuanku Tambusai, 2026)
The issue of equitable development and demographic conditions is a key issue facing the west Kutai (Kubar) Regency government, impacting job availability and improving the knowledge and skills of human resources (HR). The goal of the Community Service (PKM) operator training program is to prepare qualified Wheel Excavator Operator Trainees for the community and to help maximize the potential of their human resources in their respective fields through training. The implementation method for the Junior Level 2 Wheel Excavator Operator Training includes preparation stages, including determining the training schedule, socialization, training, and certification. The training took place at the Simpang Raya Village Meeting Hall, Barong Tongkok District, West Kutai (Kubar) Regency, East Kalimantan Province. The training provided participants with basic knowledge of safety, operation, and maintenance procedures (P2H). This significantly assisted them in improving their skills, particularly for future professional certification. It also positively impacted perceptions and increased participant enthusiasm for the training.